Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
3--1/-2-4=4/-6=2/-3
y=-2/3x+b
-2*-2/3=4/3
3-4/3=5/3
y=-2/3x+5/3
Step-by-step explanation:
Answer:
[tex]\displaystyle y=-\frac{2}{3}x+\frac{5}{3}[/tex]
Step-by-step explanation:
We want to find the equation of the line that passes through the two points:
(4, -1) and (-2, 3).
First, we will find the slope of the two points. So:
[tex]\displaystyle m=\frac{3-(-1)}{-2-4}=\frac{4}{-6}=-\frac{2}{3}[/tex]
Now, we will use the point-slope form given by:
[tex]y-y_1=m(x-x_1)[/tex]
Use either point. I'm going to use (4, -1). So, substitute:
[tex]\displaystyle y-(-1)=-\frac{2}{3}(x-(4))[/tex]
Simplify and distribute:
[tex]\displaystyle y+1=-\frac{2}{3}x+\frac{8}{3}[/tex]
Subtract 1 from both sides. Therefore:
[tex]\displaystyle y=-\frac{2}{3}x+\frac{5}{3}[/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.